Richard Armstrong papers - Armstrong, Richard, 1805-1860.
Principally letters of Armstrong and his wife, Clarissa Chapman Armstrong, and their relatives and friends, to Reuben A. Chapman and William N. Armstrong. Includes material relating to Armstrong's work as missionary of the American Board of Commissioners for Foreign Missions in Hawaii and as Hawaiian Minister of Education and Privy Councilor, and to the Hilo Manual Labor School for Native Hawaiians, living conditions in Hawaii, the influence of foreigners in the Hawaiian government, and the Armstrong and Chapman families.
American missionary and official of the Kingdom of Hawaii.
Collection material in English.
Keywords: Armstrong, Clarissa Chapman, -- 1805-1891 -- Correspondence; Armstrong, William N. -- Correspondence; Chapman, Reuben A. -- Correspondence; Armstrong family; Chapman family; American Board of Commissioners for Foreign Missions; Manual Labor School for Native Hawaiians (Hilo, Hawaii); Education -- Hawaii; Missions -- Hawaii; Vocational education -- Hawaii; Hawaii -- Politics and government -- To 1893.; Hawaii -- Social conditions; Missionaries